Development of inventory control system for research laboratory - Ng, Zheng Nian (2019)
Poor housekeeping standards usually leads to improper utilisation of spaces and poor inventory management. This has become an ongoing issue in several research laboratories based in NTU. Therefore, an inventory control system is required to track all activities and make use of existing technologies to provide accurate inventory levels to curb such issues. Possessing an inventory control system would help to complement good housekeeping practices as inventory models such as the Max/Min could be implemented to prevent inventory levels from exceeding certain thresholds. As a result, it would directly resolve the issue of improper utilisation of spaces. Therefore, the aim of this report is to document the methodologies and principles taken in order to implement an inventory control system for one of the many research laboratories based in NTU. In phase 1, optimisation of spaces for storage of inventories was performed. SolidWorks drafting and data obtained on site was being utilised to recreate the existing layout of the laboratory. The 5S approach was then performed virtually on the layout created within the SolidWorks software to identify potential spaces for storage of inventories. Different layouts were then generated, compared and quantified to identify potential solutions to restructure the workflow and layout of the laboratory. In phase 2, an inventory management software was being developed with the aid of Microsoft Excel VBA. The purpose of developing a software was to track all activities that occur within the laboratory. This is to improve traceability and prevent discrepancies from occurring within the laboratory whenever an inventory is drawn or received. Furthermore, a Max/Min system would be implemented within the software to allow the administrator to identify the reordering points and maximum inventory storage levels. As a result, this prevents over purchasing of inventories which would in turn cause a lack of storage space and increased working hazards within the laboratory. By unifying the two phases mentioned above, an inventory control system can be created for the research laboratory. This is due to the fact that both phases have to be implemented in order to complement each other to ensure that the entire system sustains and not revert to old practices.